Australian midwives knowledge, attitude and perceived learning needs around perinatal mental health - Hauck, Yvonne; Kelly, G.; Dragovic, M.; Butt, J.; Whittaker, P.; Badcock, J. (ELSEVIER SCI LTD, 2015)
Design and aim: a cross sectional survey was undertaken to explore midwives׳ knowledge of, and attitudes towards, mental health disorders in childbearing women vis-à-vis their perceived mental health learning needs. Setting and participants: a 50.1% response rate included 238 midwives employed in the only public tertiary maternity hospital in Western Australia from March to June 2013. Method and findings: The survey comprised a mixture of custom-designed questions and vignettes presenting various disorders. Only 37.6% of midwives felt well-equipped to support women, whilst 50.2% reported insufficient access to information. Demand was highest for education on: personality disorders (77.8%); the impact of childbearing on mental health disorders (74.2%); and skills for handling stress and aggression (57.8%). Knowledge scores were variable: on average eight out of a maximum 13 questions were answered correctly, but few (2.7%) answered more than 11 correctly, and 3.7% scored ≤4 correct. Across disorders, recognition from vignettes was highest for depression (93.9%), and lowest for schizophrenia (65.6%). Surprisingly, there were no associations between general knowledge scores and previous mental health experience, recent professional development, or access to information around mental health. The majority endorsed positive beliefs about midwives׳ role in mental health assessment, and belief in women׳s recovery (83.5%), however, cluster analysis of warmth and competence ratings revealed negative stereotyping of mental health disorders.Key conclusions: Midwives accept it is their role to assess the mental health status of women but many feel ill-equipped to do so and express a strong desire for further knowledge and skills across a range of perinatal mental health topics. Attitudes to recovery are positive but negative stereotypes exist; therefore awareness of potential bias is important to negate their influence on care. Implications for practice: Learning needs may change due to trends in clinical practice. Strategies are needed to recognise negative beliefs and to ensure education is responsive to local contexts.